The Role of Youth Social Participation in Shaping Democratic Attitudes Based on Citizenship Values - Taukhid Taukhid; Nur Chabibah (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
This Study Aims To Analyze The Role Of Youth Social Participation In Shaping Democratic Attitudes Based On Citizenship Values Among Students At Madrasah Diniyah Takmiliyah Al-Itqon. The Research Employed A Mixed Methods Approach With A Sequential Explanatory Design, In Which Quantitative Data Collection And Analysis Were Conducted First, Followed By Qualitative Exploration To Strengthen And Explain The Quantitative Findings. The Quantitative Phase Involved Distributing Questionnaires To 30 Adolescent Students To Measure The Level Of Social Participation And Democratic Attitudes Based On Citizenship Values. The Collected Data Were Analyzed Using Descriptive And Inferential Statistical Techniques. The Qualitative Phase Was Conducted Through In-Depth Interviews And Focus Group Discussions (FGD) To Gain A Deeper Contextual Understanding Of How Social Participation Contributes To The Formation Of Democratic Attitudes In The Daily Lives Of Students. The Findings Revealed That Youth Social Participation Plays A Significant Role In Shaping Democratic Attitudes Based On Citizenship Values. Students Who Actively Participated In Social, Religious, And Collaborative Activities Demonstrated Better Attitudes In Terms Of Tolerance, Mutual Respect, Responsibility, Cooperation, And Decision-Making Through Deliberation. The Qualitative Findings Further Indicated That The Culture Of Togetherness, Social Interaction, And Collective Activities Within The Madrasah Environment Contributed Positively To Strengthening Democratic Character Among Students. This Study Concludes That Social Participation Serves As An Important Medium In Developing Democratic Attitudes Rooted In Citizenship Values Among Adolescent Students In Islamic Educational Settings.